2017
DOI: 10.1002/cncr.30636
|View full text |Cite
|
Sign up to set email alerts
|

Smokers with chronic myeloid leukemia are at a higher risk of disease progression and premature death

Abstract: Even when considering differences in socioeconomic status and lifestyle between patients who smoke and nonsmokers, the current analysis demonstrated that smoking also might affect disease biology. The results of the current study indicate that patients with chronic myeloid leukemia, in particular those aged <60 years, should be encouraged to quit smoking. Cancer 2017;123:2467-71. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…The potential expression of these enzymes in CML cells may also be a factor in drug efficacy, or indeed drug resistance. Indeed, our findings provide a mechanistic rationale for the recent report that CML patients that are smokers are at increased risk of disease progression and premature death ( Lauseker et al, 2017 ).…”
Section: Discussionsupporting
confidence: 54%
“…The potential expression of these enzymes in CML cells may also be a factor in drug efficacy, or indeed drug resistance. Indeed, our findings provide a mechanistic rationale for the recent report that CML patients that are smokers are at increased risk of disease progression and premature death ( Lauseker et al, 2017 ).…”
Section: Discussionsupporting
confidence: 54%
“…These findings emphasized the urgent need to strengthen smoking control to reduce the CML burden. A previous study revealed that smoking might be an adverse prognostic factor, shortening survival time and contributing to CML's progression [ 42 ]. The smoking prevalence declined in most countries during the research, especially in high-income countries [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco smoking is a risk factor for death and disease‐specific death in several cancers, including acute myeloid leukaemia 14–17 . Similarly, in a study investigating long‐term effects of imatinib treatment, in patients with chronic myeloid leukaemia (CML), smoking increased the risk of death and disease progression 18 . Smoking is a suspected risk factor for both acute and chronic myeloid leukaemia, similar to what has been proposed in MPNs 19,20 …”
Section: Introductionmentioning
confidence: 75%